2009
DOI: 10.4161/cbt.8.19.9650
|View full text |Cite
|
Sign up to set email alerts
|

Obesity promotes melanoma tumor growth: Role of leptin

Abstract: Epidemiological studies suggest that obesity increases the risk of developing several cancers, including melanoma. Obesity increases the expression of angiogenic factors, such as leptin, that may contribute to tumor growth. However, a direct cause and effect relationship between obesity and tumor growth has not been clearly established and the role of leptin in accelerating tumor growth is unclear. Our objective in the present study was to examine the rate of melanoma tumor growth in lean and obese mice with l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
109
0
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(118 citation statements)
references
References 30 publications
6
109
0
3
Order By: Relevance
“…We hypothesize that ovariectomy (OVX) plus a high-fat diet with the inoculation of E0771 (mouse ER + breast cancer) cells in female wild-type >60 week old mechanisms that involve the upregulation of VEGF pathways. 15 The present study determines the following: (1) whether postmenopausal obesity increases VEGF expression, tumor angiogenesis and breast tumor growth in mice; (2) whether increased visceral fat size is correlated to increased breast tumor size; and (3) whether there is a difference in VEGF release from visceral fat compared to subcutaneous fat.…”
Section: Postmenopausal Obesity Promotes Tumor Angiogenesis and Breasmentioning
confidence: 98%
“…We hypothesize that ovariectomy (OVX) plus a high-fat diet with the inoculation of E0771 (mouse ER + breast cancer) cells in female wild-type >60 week old mechanisms that involve the upregulation of VEGF pathways. 15 The present study determines the following: (1) whether postmenopausal obesity increases VEGF expression, tumor angiogenesis and breast tumor growth in mice; (2) whether increased visceral fat size is correlated to increased breast tumor size; and (3) whether there is a difference in VEGF release from visceral fat compared to subcutaneous fat.…”
Section: Postmenopausal Obesity Promotes Tumor Angiogenesis and Breasmentioning
confidence: 98%
“…Many factors may contribute to the effects of obesity on melanoma growth. Studies showed that adipocytes released IL-6 (15) and leptin (20) to promote melanoma growth and invasion. Understanding the roles of adipocytes in promoting melanoma growth may suggest an alternate and a direct therapeutic strategy to combat malignant melanoma.…”
Section: Tumorigenesis Involves Constant Communication Between Tumor mentioning
confidence: 99%
“…Cells-Studies have demonstrated that obesity promotes melanoma tumor growth (19,20); therefore, we established a DIO mouse model for the study. We fed 5-week old male mice (C57BL/6) a high fat diet (Research Diets) and fed control mice a comparable control diet (Research Diets).…”
Section: Co-cultivation With Isolated Adipocytes Increases Lipid Accumentioning
confidence: 99%
“…The risk for developing MM was found to be positively associated with serum levels of leptin and inversely with healthy lifestyle factors (6). Melanoma tumor growth may be accelerated by leptin (7).…”
mentioning
confidence: 99%